Transcriptional regulation of Annexin A2 promotes starvation-induced autophagy - Moreau, Kevin; Ghislat, Ghita; Hochfeld, Warren; Renna, Maurizio; Zavodszky, Eszter; Runwal, Gautam; Puri, Claudia; Lee, Shirley; Siddiqi, Farah; Menzies, Fiona; Ravikumar, Brinda; Rubinsztein, David (Nature Publishing Group, 2019)
Autophagy is an important degradation pathway, which is induced after starvation, where it buffers nutrient deprivation by recycling macromolecules in organisms from yeast to man. While the classical pathway mediating this response is via mTOR inhibition, there are likely to be additional pathways that support the process. Here, we identify Annexin A2 as an autophagy modulator that regulates autophagosome formation by enabling appropriate ATG9A trafficking from endosomes to autophagosomes via actin. This process is dependent on the Annexin A2 effectors ARP2 and Spire1. Annexin A2 expression increases after starvation in cells in an mTOR-independent fashion. This is mediated via Jun N-terminal kinase activation of c-Jun, which, in turn, enhances the trans-activation of the Annexin A2 promoter. Annexin A2 knockdown abrogates starvation-induced autophagy, while its overexpression induces autophagy. Hence, c-Jun-mediated transcriptional responses support starvation-induced autophagy by regulating Annexin A2 expression levels.